Contribuições da análise do comportamento para reabilitação verbal de crianças usuárias de implante coclear - PEREIRA, Fabiane da Silva (Universidade Federal do Pará, 2018)
This study is characterized by a research portfolio, which involves Behavior Analysis, linguistic behavior and cochlear implant. It got together a study of the literature review, and two experimental studies that tried to verify the effect of Multiples Examples Instructions (MEI) procedures, which started with different methods, and also with a list of deaf children naming and cochlear implanted children. The naming concept and the method used on the last 20 years were reviewed. The study 1, experimental, investigated on three children that are cochlear implanted, the effect of the Multiples Examples Instructions procedures on the repertory integration of hear and speak. The study 2, experimental, evaluate in a child that was late cochlear implanted the effect of teach only of the listening repertory about naming, and the MEI about naming repertory. The literature review showed that the naming concept uses like described by Horne and Lowe (1996) has increased on the Behavior Analysis literature. And three procedures have been used during 20 years: hand sorting, MEI and Pairing naming. The study 2 results indicated that the MEI procedure was essential to the hearer and speaker repertory integration, which reduced the performance differences between speak and listen people. And the study 3 results showed that were necessary extra exposes to MEI to naming emergency. It discuss the possibility of new procedures at speak and hear abilities of cochlear implanted children.